Clinical indicators of dry eye severity nursing outcome in intensive care unit - Raffaela Patrícia da Silva Soares; Ana Paula Nunes de Lima Fernandes; Fabiane Rocha Botarelli; Jéssica Naiara de Medeiros Araújo; Jéssica de Araújo Olímpio; Allyne Fortes Vitor
Objective: to verify the extent of impairment of the clinical indicators of the nursing outcome Dry Eye Severity in patients admitted to the Intensive Care Unit. Method: cross-sectional, descriptive study developed with 206 patients. Based on the result listed, six indicators of the Classification of Nursing Results were evaluated with a questionnaire containing clinical variables and the Likert scale of the Classification of Nursing Results with constructed definitions, which varies from more impaired to non-impaired. The data were analyzed using descriptive and inferential statistics. Results: the decrease in lacrimal production and the presence of redness in the conjunctiva were more impaired. The other indicators were more frequent for the absence of impairment: incomplete eyelid closure 81% (167), excessive tearing 95.1%(196), excessive mucous secretion 78.7% (162) and decreased blinking mechanism 50.5% (104). The clinical characteristics of hospitalization for neurological disorders, invasive mechanical ventilation, chemosis, use of sedatives, vasoconstrictors, benzodiazepines, antibiotics and corticosteroids interfered in the impairment of the dry eye severity. Conclusion: the result indicators show that the clinical characteristics of patients in the intensive care unit interfere in the impairment and in the dry eyes severity. According to these results, the importance of assistance directed to the prevention of eye diseases is emphasized.